Strategi Penatalayanan Gereja Bagi Pertumbuhan Jemaat - Irvan Nixon Grosman; Heldy Rogahang; Deflita Lumi (Peneliti.net, 2021)
The purpose of this study is to describe the Church Stewardship Strategy for Congregational Growth. Also to classify supporting factors, analyze inhibiting factors, and how to overcome obstacles to church stewardship strategies for the growth of their congregations, as well as describe developments and innovations carried out in Church Stewardship Strategies for Congregational Growth. Data were collected through observation, interviews, and documentation studies. The results of the study show that human resources, accountable financial management, accompanied by accurate data administration as well as the cohesiveness of the service team greatly affect the growth of the congregation and this is a stewardship strategy. It is hoped that this research will provide benefits and a wider understanding for church organization leaders, pastors / pastors, deacons / church workers to serve in order to reach souls for the kingdom of God.